Curcuminoid Contents in Rhizomes of Some Zingiberaceous Plants Sold via Online Platforms: Influence of Species and Cultivation Location - Chaowalit Monton; Orawan Theanphong; Pathamaporn Pathompak; Jirapornchai Suksaeree; Natawat Chankana (International Journal of Food Science)
Zingiberaceous plants are versatile and find application in various fields, including food, medicine, and cosmetics. Recently, turmeric and other Zingiberaceous plants have become readily available through online platforms. However, the quality, specifically the curcuminoid content, has not been adequately assessed. In light of this issue, this study is aimed at analyzing the curcuminoid contents, including bisdemethoxycurcumin, demethoxycurcumin, and curcumin, using high-performance liquid chromatography. The analysis targets the rhizomes of Zingiber montanum (ZM), Curcuma aromatica (CA), Curcuma wanenlueanga (CW), Curcuma zedoaria (CZ), and sixteen Curcuma longa (CL) samples sold on online platforms. The influence of species and cultivation locations was evaluated, compared, and clustered. The results indicated that CL exhibited the highest curcuminoid contents, followed by CA, CZ, ZM, and CW, respectively. Curcumin was not detected in CW, while bisdemethoxycurcumin and demethoxycurcumin were absent in ZM. Cluster analysis revealed that CW was closely related to ZM, and CA was closely related to CZ, while CL was not closely related to either cluster. Among the sixteen CL samples, the most commonly found curcuminoids were curcumin, followed by bisdemethoxycurcumin and demethoxycurcumin, respectively. Three samples contained curcuminoid contents of less than 5%, failing to meet the standard level specified in the Thai Herbal Pharmacopoeia. Furthermore, ten samples had total curcuminoid contents higher than 10%, with three samples exceeding 15%. The top three samples with the highest total curcuminoid contents from different locations were as follows: Tha Yang District, Phetchaburi Province (17.02%); Phop Phra District, Tak Province (16.97%); and Pak Tho District, Ratchaburi Province (15.45%). Cluster analysis revealed that CL samples could be grouped into two major categories: low curcuminoid and high curcuminoid groups. This study offers valuable insights for consumers seeking high-quality rhizomes of Zingiberaceous plants with high curcuminoids, through online platforms. By focusing on the curcuminoid content, consumers can make informed decisions when purchasing Zingiberaceous plants online. This information not only aids in selecting superior quality rhizomes but also enhances the overall consumer experience by ensuring the potency and efficacy of the purchased products.